HYPNOSIS COMMUNICATION PATTERNS IN BUILDING CLIENT SELF-AWARENESS AND MENTAL HEALTH - Tarsani; Yoedo Shambodo; Fachmi Ibrahim; Risqi Inayah Dwijayanti; Radita Gora Tayibnapis (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The changes and pressures of daily life often leave people feeling bored and stressed, making it difficult to maintain a healthy mindset. Various illnesses arise from human negligence, such as not maintaining a healthy lifestyle, or are caused by viral, bacterial, and other factors that disrupt physical health. However, beyond these factors, there are also non-medical causes of bodily